2007
DOI: 10.1111/j.1573-7861.2007.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Shareholder Value and the Transformation of the U.S. Economy, 1984–20001

Abstract: Using data from 62 U.S. industries for 1984-2000, this article explores the connections between shareholder value strategies, such as mergers and layoffs, and related industry-level changes, such as de-unionization, computer technology, and profitability. In line with shareholder value arguments, mergers occurred in industries with low profits, and industries where mergers were active subsequently saw an increase in layoffs. Industries with a high level of mergers increased investment in computer technology. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(164 citation statements)
references
References 64 publications
2
156
0
6
Order By: Relevance
“…Recently, a number of prominent scholars of industrial relations as well as sociologists have maintained that the growing pressure from financial markets and the rise of shareholder value have brought drastic changes to the employment policies of leading U.S. companies (Budros 1997;Cappelli 1999;Fligstein and Shin 2007;Hirsch and De Soucey 2006;Osterman 1999). With a corresponding power shift within corporations to executives responsible for finance, U.S. firms have placed a low priority on human resources relative to financial and shareholder considerations (Kochan forthcoming).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a number of prominent scholars of industrial relations as well as sociologists have maintained that the growing pressure from financial markets and the rise of shareholder value have brought drastic changes to the employment policies of leading U.S. companies (Budros 1997;Cappelli 1999;Fligstein and Shin 2007;Hirsch and De Soucey 2006;Osterman 1999). With a corresponding power shift within corporations to executives responsible for finance, U.S. firms have placed a low priority on human resources relative to financial and shareholder considerations (Kochan forthcoming).…”
Section: Resultsmentioning
confidence: 99%
“…In a series of studies using data on Fortune 100 firms from 1979 to 1994, Budros (1997; demonstrated that decline in shareholder value (measured as percentage change in a firm's stock price) triggered corporate downsizing. Using industry-level data, Fligstein and Shin (2007) also showed that industries with low profits relative to assets were more likely to engage in layoffs. Like most economic studies, they demonstrate that declining performance leads to downsizing but then argue that pressure from the financial community may explain such a relationship.…”
Section: Sociological Research On Downsizing: a New Paradigm Of The Firmmentioning
confidence: 98%
See 2 more Smart Citations
“…3. In our discussion of financial markets, we note that changes in taxation coincided with the shareholder value movement that encouraged CEOs to focus on short-term stock price increases (Fligstein and Shin 2007), which is also related to increasing reliance on stock options as compensation. 4.…”
Section: Fundingmentioning
confidence: 99%